(untitled) (Research, Society and Development, 2024)
Futsal is a sport, categorized as an invasion sport. Its characteristics originating from field football have attracted more and more supporters, whether as fans, spectators or practitioners. However, for the sport to enter the court, there will always be a cost, and in the case of federated competitions, the greater the competitiveness, the greater the need for financial support. The present study aims to identify and quantify the different financial needs and the real amount spent to put a futsal project into operation. The data was collected through a spreadsheet, listing each sector of the club and the amount invested in the season. Ten teams competing in League One from the state of Rio Grande do Sul and two teams from the state participating in the National League were evaluated. The main investments are the hiring of players (42%) and the technical committee (13% to 24.5%), while a team competing in the Liga Gaúcha invests R 855,959.00 ± 248,449.00 reais, with minimum values of R R 558,500.00 and a maximum of R 1,268,840.00, national league teams invest approximately R 2,726,940.00 each year, that is, the investment made in the Liga Gaúcha is equivalent to 31.4% of the amount invested for a team in the National League.